Chemical characterization free radical scavenging and antibacterial activity of Zuccagnia punctata cav (Fabaceae) exudate - Gómez, J. (2019)
The resins are nonvolatile products of pants, exude naturally (surface resins) or can be obtained by incision or infection (internal resins). Their chemical composition including flavonoids, terpenoids, and fatty substances is in some cases a protective barrier for the plant against the attack of some herbivores .A limited number of families including Fabaceae, Burseraceae, and Pinaceae stand out for their high resin production. Argentina's Andean region is the habitat of plant species belonging to the genera Larrea, Zuccagnia, and Bulnesia recognized for their high production of resins or exudates, of which there is a lack of knowledge about their potential as sources of compounds of agronomic and industrial interest. A dichloromethane exudate (DCME) obtained by dipping of fresh aerial parts from Z. punctata was evaluated regarding their antioxidant, antibacterial and UHPLC-MS metabolome fingerprinting. The antioxidant properties were assayed by DPPH, TEAC, FRAP and lipoperoxidation inhibition in erythrocytes methods and the antibacterial activity according to the Clinical and Laboratory Standards Institute (CLSI) guidelines. The DCME showed a stronger free radical scavenging activity on DPPH radical (IC50 = 25 µg/mL) and inhibited the lipid peroxidation in erythrocytes in 70%, at 250 µg/mL. The DCME was active against Gram (+) and Gram (-) bacteria (MICs values between 125-250µg/ml). Forty-seven compounds were detected and identified based on the UHPLC OT-MS including, chalcones, dihydrochalcones, flavones, flavanones, nine correspond to flavonoids, thirteen to caffeic acid ester derivatives. Several compounds are first reported for this species. The results support that Z. punctata exudate is a valuable natural product with the potential to improve human health and industrial interest.